G513 The rhino project, a quality improvement project targeting early detection and referral of neonates with hypoglycaemia. (27th April 2015) - Fan, T; Sharma, A; Charkin, E
Abstract : Context: We describe an ongoing multidisciplinary quality improvement project at a maternity hospital with a busy level 3 neonatal unit. The project involved all staff caring for newborns including midwives, nursery nurses, health care assistants and doctors. Problem: Hypoglycaemia is a common presentation in newborns and second most common reason for term infant admissions to neonatal units in England. Delayed recognition and treatment of hypoglycaemia can lead to serious neurological deficit and death. Intervention: An NHSLA audit was carried out in July 2012 to assess the care of neonates at risk of hypoglycaemia. This showed multiple problem areas including neonates not being managed as per the guideline and "at risk" neonates being monitored using incorrect proformas or not being monitored at all. The audit also revealed unnecessary glucose monitoring of some neonates who no longer required it. A survey of all staff involved in newborn care was carried out and factors contributing to the problem were identified at all levels. At an organisational level, there were obsolete proformas on the ward with different thresholds for referral and three differing guidelines available on the intranet. At team level, the survey revealed that midwifes felt it was difficult to contact a neonatal SHO for referral and that there was lack of consistency in advice provided. At an individual level, staff indicated a lack of education regarding the guideline and testing revealed a lack of familiarity, especially amongst trainees. Strategy for change: Obsolete proformas were removed from clinical areas and out of date guidelines from the intranet. The current guideline was streamlined and summarised with the addition of a bedside algorithm. An education programme was implemented to disseminate this information, called the RHINO project, an acronym for Referral/Review for Hypoglycaemia/Hypothermia detected during Newborn Observations. Colourful posters were prominently placed on postnatal wards and teaching sessions were organised at postnatal ward handover to call attention to posters and key messages. Nursery nurses based on postnatal wards also continue to act as champions for the project to reinforce the message. Hypoglycaemia guideline education was added to the induction programme for new doctors. Measurement of improvement: Further audits carried out at 1, 4 and 18 months showed 100% compliance with almost all criteria, compared with 68 to 89% in the original audit (see Table 1 ). An audit of neonates admitted to the neonatal unit with hypoglycaemia during the 6 months following implementation of the programme showed 100% and 91% compliance with thresholds for referral and admission respectively. Case review identified the non-compliance was caused by confusion over the discrepancy between blood sugar levels measured on bedside and blood gas machines. This led to a guideline amendment that blood sugars less than 2.5 mmol/L should now be confirmed with capillary gas sample. A further staff survey showed improvement in guideline familiarity. Lessons learnt: Success of this quality improvement project relied on information from all members of the multidisciplinary team. Their survey responses helped us identify interventions required. We feel the presence of human champions to continue reinforcing the message has helped us maintain good practice. Message for others: Our main message is the value of human factors to maintain good practice and involving all members of multidisciplinary team in quality improvement work. Our project has also shown the importance of addressing problems at all levels.